Antiarrhythmic Effect of Ranolazine in Combination with Class III Drugs in an Experimental Whole‐Heart Model of Atrial Fibrillation. Issue 6 (December 2013) - Frommeyer, Gerrit; Milberg, Peter; Uphaus, Timo; Kaiser, Dennis; Kaese, Sven; Breithardt, Günter; Eckardt, Lars
Summary Background Ranolazine is evaluated for antiarrhythmic therapy of atrial fibrillation (AF). The electrophysiologic mechanisms of ranolazine in combination with class III drugs were studied in an isolated whole‐heart model of stretch‐related AF. Methods and Results Thirty rabbits were fed with amiodarone (50 mg/kg/day, n = 10), dronedarone (50 mg/kg/day, n = 10), or placebo (n = 10) for 6 weeks. Subsequently, in isolated hearts, AF was induced by high‐rate atrial pacing and acute atrial dilatation. In placebo‐treated hearts, d, l‐sotalol (50 μM) was acutely administered. Ranolazine (10 μM) was additionally infused in all groups. Chronic amiodarone (+26 ± 7 ms, P < 0.05) or dronedarone (+22 ± 4 ms, P < 0.05) as well as acute application of d, l‐sotalol (+20 ± 3 ms, P < 0.05) increased atrial action potential duration (aAPD90). Additional treatment with ranolazine did not significantly change aAPD90 (P = ns). Class III drugs did not affect interatrial conduction time, while ranolazine significantly increased it (amiodarone group: +15 ± 3 ms, dronedarone group: +11 ± 3 ms, sotalol group: +15 ± 6 ms; P < 0.05 each). Ranolazine led to an additional increase in atrial effective refractory period (aERP), thus leading to an enhanced atrial postrepolarization refractoriness (aPRR, +17 ± 6 ms, +21 ± 4 ms and +16 ± 8 ms, P < 0.05, respectively). Acute atrial dilatation increased AF incidence compared with baseline. Amiodarone‐pretreated hearts showed a lower incidence of AF. Additional infusion of ranolazine further diminished AF. Dronedarone or acute infusion of sotalol did not significantly suppress AF, while additional treatment with ranolazine in these groups also reduced AF incidence. Conclusion In this study, ranolazine on top of class III antiarrhythmic therapy had a beneficial effect. The increase in interatrial conduction time and marked atrial aPRR suppressed AF. These results shed further light on a potential therapeutic benefit of ranolazine on top of conventional antiarrhythmic therapy for rhythm control in AF.